PERHITUNGAN STRUKTUR JEMBATAN KOMPOSIT DESA PERJIWA - LUDY WIYANTO, DWI YUSNI (KURVA S JURNAL MAHASISWA, 2013)
ABSTRACTTransportation is an important part of human life and developingmechanisms in line with the human civilization itself. One part is a transportbridge. The bridge is an important element in the transportation system, serving asa bridge serves traffic flow on it.The bridge was originally a wooden bridge, because the bridge is often thecase when there is a wobble on top of passing vehicles. Hence the need toimprove the ability of the bridge and redesigned into a composite bridge .Long span composite bridge being simulated is 25 m,width 6 m carriageway, pavement width of 0.5 m and 0.5 m right side of the leftside, so that the total width of the bridge 7 m. Results of analysis of compositebridge calculation is derived calculations use the floor slab reinforcement D16 -150 for flexural reinforcement and negative reinforcement D16 - 150 for flexuralposiitif. Pavement reinforcement use the D16 - 200. Backrest using reinforcement4Ã˜12 pole . Tread plate for transverse and longitudinal directions usingreinforcement D16 - 100. Using a steel girder profile WF 900 X 300, shearconnector used for connecting reinforcement D16 - 1562 , 5.Keywords : Composite, Bridge, Structure.